2023
DOI: 10.1155/2023/1626488
|View full text |Cite
|
Sign up to set email alerts
|

Ease to Challenges in Achieving Successful Synthesized Schiff Base, Chirality, and Application as Antibacterial Agent

Abstract: This study reports how to overcome the challenges experienced in achieving successful synthesized Schiff base via types of Schiff base (chiral and achiral), synthesis, nature of products, and its antibacterial applications. Schiff base is a versatile ligand which is useful in asymmetric reactions to prepare chiral catalysts. It is also used in symmetric reactions to prepare achiral compounds. In line with the achiral compounds, conventional (room temperature and refluxing) and microwave irradiation methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…The model compound for tetrazoles used was 5-phenyl-1H-tetrazole. Neshat et al (2023) [106] reported the synthesis and characterization of a Cu(II) complex CuL 2 (45) with a bidentate SB derived from Ortho-vanillin. The catalytic activity was studied in the oxidation of selected primary and secondary alcohols.…”
Section: Metal Complexes With Sbs With Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The model compound for tetrazoles used was 5-phenyl-1H-tetrazole. Neshat et al (2023) [106] reported the synthesis and characterization of a Cu(II) complex CuL 2 (45) with a bidentate SB derived from Ortho-vanillin. The catalytic activity was studied in the oxidation of selected primary and secondary alcohols.…”
Section: Metal Complexes With Sbs With Catalytic Activitymentioning
confidence: 99%
“…The highly stable complexes formed by SBs with transition metals often lead to compounds with strongly enhanced activities in inorganic [22,23] and bioinorganic chemistry [24], materials science [25], and pharmacology for biomedical applications [26][27][28][29][30]. The most described biological activities regarding the SBs complexes are antitumoral [31][32][33][34][35], antioxidant [36,37], antidiabetic [38][39][40][41], antimalarial [42], antiarthritic [43], antimicrobial [44][45][46][47][48], neuroprotective, catalase-like and catecholase-like enzymatic [49,50], and DNA-binding [51,52]. Recently, Aggarwal et al (2022) [53] underlined the potential applicability of some SBs and their metal complexes for the treatment of COVID-19 [54], which may represent valid alternatives to the classic treatments for this disease [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…The swift progressions in pharmaceutical and medicinal chemistry have diverted the attention of scientists toward the development of drugs, even for intricate conditions such as diabetes mellitus, a critical global health concern that emerges from aberrant insulin production. Schiff bases have demonstrated encouraging results across a range of research domains, as they investigate their insulin-mimetic characteristics. Schiff bases have notably exhibited antidiabetic potential, as demonstrated by Szklarzewick’s group …”
Section: Introductionmentioning
confidence: 99%
“…They are condensation products of ketones (or) aldehydes with primary amines [1]. Hugo Schiff discovered Schiff base in 1864, by condensation reaction of alkanal or alkanone and primary in azeotropic distillation, which was named after him [2]. A large number of different Schiff base ligands have been used as cation carriers in potentiometric sensors as they have shown excellent selectivity, sensitivity, and stability for specific metal ions such as Ag(II), Al(III), Co(II), Cu(II), Gd(III), Hg(II), Ni(II), Pb(II), Y(III), and Zn(II) [3].…”
Section: Introductionmentioning
confidence: 99%